2021
DOI: 10.3384/ecp183159
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of the Dorabella Cipher with Statistical Language Models

Abstract: The Dorabella cipher is a symbolic message written in 1897 by English composer Edward Elgar. We analyze the cipher using modern computational and statistical techniques. We consider several open questions: Is the underlying message natural language text or music? If it is language, what is the most likely language? Is Dorabella a simple substitution cipher? If so, why has nobody managed to produce a plausible decipherment? Are some unusual-looking patterns in the cipher likely to occur by chance? Can stateof-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results of the present study comport with other recent analyses of the Dorabella cryptogram. Schmeh (2018) concluded that "frequency count and the contact counts of the Dorabella Cryptogram are consistent with the English language," and Hauer et al (2021) reported "evidence for English as the language of the cipher" from n-gram language models, and that "the occurrence of several pairs of mirrored symbols is unlikely to be due to chance, suggesting that Dorabella is not a hoax." Still, no convincing MASC solution to the Dorabella cryptogram has yet been found, even using modern, state-of-the-art algorithms with high decipherment rates (Wase, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study comport with other recent analyses of the Dorabella cryptogram. Schmeh (2018) concluded that "frequency count and the contact counts of the Dorabella Cryptogram are consistent with the English language," and Hauer et al (2021) reported "evidence for English as the language of the cipher" from n-gram language models, and that "the occurrence of several pairs of mirrored symbols is unlikely to be due to chance, suggesting that Dorabella is not a hoax." Still, no convincing MASC solution to the Dorabella cryptogram has yet been found, even using modern, state-of-the-art algorithms with high decipherment rates (Wase, 2023).…”
Section: Resultsmentioning
confidence: 99%